Identification of Two Novel Fluorinases From Amycolatopsis sp. CA-128772 and Methanosaeta sp. PtaU1.Bin055 and a Mutant With Improved Catalytic Efficiency With Native Substrate - Feng, Xinming; Cao, Yujin; Liu, Wei; Xian, Mo (Frontiers in Bioengineering and Biotechnology, 2022)
Fluoride plays an important role in the fields of materials and medicine. Compared with chemical synthesis, fluorinases are natural catalysts with more application potential, which provide a green and effective way to obtain organofluorine. However, the application of fluorinases is limited by certain factors, such as the limited number of enzymes and their low activity. In this work, two new fluorinases from Amycolatopsis sp. CA-128772 and Methanosaeta sp. PtaU1.Bin055 were identified by gene mining and named Fam and Fme, respectively. The activities of these two enzymes were reported for the first time, and Fme showed good thermal stability, which was different from the reported fluorinases. In addition, the activity toward natural substrate of Fam was improved by site-directed mutagenesis, the catalytic efficiency (kcat/Km) of the best mutant containing two amino acid substitutions (T72A and S164G) toward the substrate S-adenosyl-L-methionine was improved by 2.2-fold compared to the wild-type. Structural modeling analysis revealed that the main reason for the increased enzyme activity might be the formation of a new substrate channel. Experimental evidence suggests that the substrate channel may indeed play a key role in regulating the function of the fluorinases.